ANALYSIS OF FOOD PURCHASE DECISION MODELS USING MEDIA APPLICATIONS IN PRIVATE UNIVERSITIES DURING THE COVID-19 PANDEMIC - Tupti, Zulaspan; Arif, Muhammad; Rambe, Ihsan (CV. Radja Publika, 2021)
The purpose of the study aims to analyze several things, namely: The Influence of Country Of Origin on Purchase Decisions, Brand Image on Purchase Decisions and Service Quality on Purchase Decisions, Effect of Country Of Origin, Brand Image and Service Quality on Purchase Decisions. In this study using 91 respondents who are students of the Faculty of Economics and Business management who use the grab application at the Universitas Muhammadiyah Sumatera Utara. Data collection techniques using a list of statements such as online questionnaires and data analysis techniques using the Statistical Package For The Social Sciences (SPSS) to test the four hypotheses proposed in this study. Based on the results of the study, the following conclusions were obtained: Country Of Origin partially positive and significant effect on food purchase decisions on the Grab application at the Universitas Muhammadiyah Sumatera Utara during the Covid 19 Pandemic. Brand Image partially negative but not significant effect on food purchase decisions on the Grab application at the Universitas Muhammadiyah Sumatera Utara during the Covid 19 Pandemic. Service quality partially has a positive and significant effect on food purchasing decisions on the Grab application at the University of Muhammadiyah North Sumatra during the Covid 19 Pandemic. Country Of Origin, Brand Image and Service Quality have a positive and significant impact on food purchasing decisions on the Grab application at the Universitas Muhammadiyah Sumatera Utara during the Covid 19 Pandemic.